2018
DOI: 10.1177/1043659618793713
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Family Factors That Affect Self-Management Behaviors Among Patients With Type 2 Diabetes: A Qualitative Descriptive Study in Chinese Communities

Abstract: This study provides insight into SMBs of Chinese diabetic patients. Professionals can develop tailored interventions in a Chinese cultural context according to patients' perceptions of family responsibility, early experience, activities, and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 67 publications
(75 reference statements)
3
15
0
Order By: Relevance
“…This is consistent with a qualitative study investigating 20 Chinese patients (40-84 years old) with type 2 diabetes conducted in 2019 [71]. The study found that almost half of the participants ignored their physical needs to avoid troubles/conflicts in families, resulting in overeating food or eating the wrong foods [71]. Similarly, a study conducted in Taiwan involving 58 older adults revealed that 40% of participants chose to follow the family eating rules and self-sacrificed for the family [72].…”
Section: The Desire To Maintain Harmony In Families/communities Plays a Role In Making Food Choicessupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with a qualitative study investigating 20 Chinese patients (40-84 years old) with type 2 diabetes conducted in 2019 [71]. The study found that almost half of the participants ignored their physical needs to avoid troubles/conflicts in families, resulting in overeating food or eating the wrong foods [71]. Similarly, a study conducted in Taiwan involving 58 older adults revealed that 40% of participants chose to follow the family eating rules and self-sacrificed for the family [72].…”
Section: The Desire To Maintain Harmony In Families/communities Plays a Role In Making Food Choicessupporting
confidence: 92%
“…As demonstrated by the research included in this review, participants reported eating unwanted food or overeating to avoid conflicts and keep harmony in families/communities. This is consistent with a qualitative study investigating 20 Chinese patients (40-84 years old) with type 2 diabetes conducted in 2019 [71]. The study found that almost half of the participants ignored their physical needs to avoid troubles/conflicts in families, resulting in overeating food or eating the wrong foods [71].…”
Section: The Desire To Maintain Harmony In Families/communities Plays a Role In Making Food Choicessupporting
confidence: 85%
“…Although the patient may not show certain clinical symptoms, the chronic condition experienced by diabetes mellitus patients must occur and has impact on their physical and psychological health. Therefore, the support received, especially from the family, will help the patients accept and immediately adapt to their sick condition [27], [31], [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…Family members can provide patients with financial support, emotional support, supervision and reminders of self-management behaviors, and instrumental support such as administering insulin injections [12,13]. The Chinese culture attaches great importance to the relationship between family members [14]. Confucianism beliefs recognize that everyone is naturally born to, grows up in, and is taken care of within a family [15].…”
Section: Introductionmentioning
confidence: 99%